2021
DOI: 10.1038/s41598-020-79597-0
|View full text |Cite
|
Sign up to set email alerts
|

Omega-7 oil increases telomerase activity and accelerates healing of grafted burn and donor site wounds

Abstract: This study investigated the efficacy of Omega-7 isolated from the sea buckthorn oil (Polyvit Co., Ltd, Gangar Holding, Ulaanbaatar, Mongolia) in ovine burn wound healing models. In vitro, proliferation (colony-forming rate) and migration (scratch) assays using cultured primary ovine keratinocytes were performed with or without 0.025% and 0.08% Omega-7, respectively. The colony-forming rate of keratinocytes in the Omega-7 group at 72 and 96 h were significantly higher than in the control (P < 0.05). The perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Studies have shown that sea buckthorn contains compounds such as omega-3, omega-6, and tocopherols, which facilitate the healing process by reducing wound inflammation. 13,18 In the present program, the size of second-degree burns was reduced during the treatment period in two groups treated with either sea buckthorn cream or 1% SSD cream, but the recovery of wound breadth was faster in the sea buckthorn group. Chandra et al in their study maintained that Sea buckthorn contains a high level of essential fatty acids which in addition to nourishing the human's skin tissue, can accelerate the process of treatment of burns.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Studies have shown that sea buckthorn contains compounds such as omega-3, omega-6, and tocopherols, which facilitate the healing process by reducing wound inflammation. 13,18 In the present program, the size of second-degree burns was reduced during the treatment period in two groups treated with either sea buckthorn cream or 1% SSD cream, but the recovery of wound breadth was faster in the sea buckthorn group. Chandra et al in their study maintained that Sea buckthorn contains a high level of essential fatty acids which in addition to nourishing the human's skin tissue, can accelerate the process of treatment of burns.…”
Section: Discussionmentioning
confidence: 66%
“…Goudarzi et al 43 in their study reported that in addition to its anti‐inflammatory properties, sea buckthorn facilitates the wound healing process due to its analgesic and anti‐hypersensitivity effects, moreover. Studies have shown that sea buckthorn contains compounds such as omega‐3, omega‐6, and tocopherols, which facilitate the healing process by reducing wound inflammation 13,18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levels of lung tissue 3-nitrotyrosine (06–284; MilliporeSigma, MA) and VEGF-A (ab46154; Abcam, MA), which is a major mediator of microvascular hyperpermeability 33 35 , were determined by automated capillary Western blot analysis (Wes™ ; ProteinSimple, San Jose, CA), as previously described 24 , 36 .…”
Section: Methodsmentioning
confidence: 99%
“…Although they are important components of the sea buckthorn, fatty acids (FA) have been less investigated in terms of biological effects (for a recent review on their impact on human health, see (Solà Marsiñach and Cuenca, 2019). It is known that sea buckthorn oil is rich in saturated and unsaturated FA and has an unusually high concentration of palmitoleic acid with proven benefits on skin health (Weimann et al, 2018;Niimi et al, 2021). Little is known about the implication of other FAs in cellular regeneration, given the fact that they are a major component of cell membrane lipids.…”
Section: Introductionmentioning
confidence: 99%